Korelasi Positif Mengumpulkan Harta Di Surga Dengan Kerajaan Allah Di Kalangan Gembala Gereja Suara Kebenaran Injil - Timotius Tan; Erastus Sabdono; Muner Daliman; Timotius Sukarna (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
Many people are facing problems with money, including Christian Leaders. Problems appear when a pastor serves others in order to gain prosperity. This attitude caused his teachings by emphasizing a successful life. Wealthy tend to be a standard of success. Surely the prosperity Gospel is false because Jesus Christ taught His believers to gain spiritual wealth in Heaven by giving priority to the kingdom of God (Matthew 6:19-34). This lack of attitude occurred among the pastors of the Synod of the Bible’s Truthful Voice Church (abbreviated as GSKI). Therefore, this article aims to seek the correlation between the GSKI pastors' perception of the concept of gaining treasure in Heaven consider to the Kingdom of God. Using the Quantitative Method, Correlational type, the Hypothesis is tested with SPSS 20 application. The results showed that the attitude of seeking treasure in heaven is a pattern of life that is formed by the pastor motive who gives priority to serving God, the kingdom of God, and His righteousness simultaneously. Hence, this article contributes to the research on how to practice the Kingdom values.